A novel UHPLC-HRMS-based metabolomics strategy enables the discovery of potential neuroactive metabolites in mice plasma, following i.p. administration of the main Crocus sativus L. bioactive component - Karkoula, E; Dagla, I. V.; Baira, E; Kokras, N; Dalla, C; Skaltsounis, AL; Gikas, E.; Tsarbopoulos, A (J Pharm Biomed Anal, 2020)
Trans-crocin 4 (TC4) is an important carotenoid constituent of saffron showing potential activity against Alzheimer's Disease (AD) due to its antioxidant and antiamyloidogenic properties. Metabolomics is an emerging scientific field that enhances biomarker discovery and reveals underlying biochemical mechanisms aiming towards the early subclinical diagnosis of diseases. To date, there are no reports on the changes induced to mice plasma metabolome after TC4 administration. We report a novel untargeted UHPLC-ESI HRMS metabolomics strategy to determine the alteration of the metabolic fingerprint following i.p. administration of TC4 in male and female mice. Blood samples from fiftysix mice treated with TC4 as well as from control animals were analyzed with UHPLC-ESI HRMS. Statistical evaluation of the results was achieved by multivariate analysis (MVA), i.e., principal component analysis (PCA), Partial Least Squares-Discriminant Analysis (PLS-DA) in order to discover the variables that contributed to the discrimination between treated and untreated groups which were identified by online database searching (e.g., Metlin, HMDB, KEGG) aided by chemometric processing, e.g., covariance searching etc. Due to the high variability imposed by various factors, e.g., sex of the animals participating in the study, administration dose and time-points of sacrifice, multilevel sparse PLS-DA analysis, e.g., splitting variation to each individual component, has been employed as a more efficient approach for such designs. This methodology allowed the identification of the time sequence of metabolome changes due to the administration of TC4, whereas a sex-related effect on the metabolome is indicated, denoting that the administration in both sexes is indispensable in order to acquire safe conclusions as reliable metabolome pictures. The results demonstrated a number of annotated metabolites playing a potential role in neuroprotection while they are closely related to AD. Moreover, five additional annotated metabolites were involved in the steroid biosynthesis pathway while two of them may be considered as putative neuroprotective agents.
Keywords: Animals; Biosynthetic Pathways/drug effects; Carotenoids/administration & dosage/*pharmacokinetics; Chromatography, High Pressure Liquid/methods; Crocus/*chemistry; Female; Injections, Intraperitoneal; Male; Mass Spectrometry/methods; Metabolomics; Metabolomics/*methods; Mice; Mice plasma; Models, Animal; Neuroactive steroids; Neuroprotective Agents/administration & dosage/*pharmacokinetics; Sex Factors; Steroids/biosynthesis; Trans-crocin 4; Uhplc-hrms